Management of unsuspected pulmonary embolism in cancer patients. Issue 1 (February 2013) - Trujillo-Santos, Javier; Monreal, Manuel
Abstract : The occurrence of symptomatic pulmonary embolism (PE) causes significant morbidity and mortality. In recent years, the detection of unsuspected PE (UPE) has become increasingly common in patients with cancer. In the absence of convincing evidence that anticoagulation can be safely withheld, current guidelines from the American College of Chest Physicians recommend treating these patients as comparable patients with symptomatic PE. The natural history of cancer patients with UPE has been compared with that of cancer patients with symptomatic PE in five cohort studies so far. In all, 285 patients had UPE, and most of them had received anticoagulant therapy for at least 3 months. Their outcome in terms of recurrences, major bleeding or mortality seem not to differ significantly from the outcome in cancer patients with symptomatic PE. However, the lack of randomized clinical trials and the limited number of observational studies do not allow firm treatment recommendations.